The Aesthetics of Creating Forms in the Images of a TV series - Omar yassein AbdelJalil; Dr Hikmat Muttashar Majeed Al Beedhan (Genius Journals, 2022)
The most popular decorative motif in porcelain painting was and remains floral arrangements. Flowers are an indispensable and inexhaustible source of inspiration for contemporary artists. Variations of flower paintings on porcelain are extremely diverse: from stylized "iconic" images to sharply characteristic, naturalistic, with an accurate reproduction of the smallest details, up to the roots and stamens. The original and even a kind of "scientific" porcelain includes a number of works made in different countries, at different times, but united by one common name - "botany"
Keywords: form; TV picture; TV series